Strong resistance of (tridecafluoro‐1, 1, 2, 2‐tetrahydrooctyl)triethoxysilane (TTS) nanofilm to protein adsorption. (8th October 2013) - Alluri, Chandrakanth; Ji, Hai‐Feng; Sit, PingFai Sidney
Abstract: In this report, the properties of fluorocarbon‐containing (tridecafluoro‐1, 1, 2, 2‐tetrahydrooctyl)triethoxysilane (TTS) (C14 H19 F13 O3 Si) nanofilm coated on silicon surface and its potential to resist protein adsorption were examined. Thickness and wettability of the silicon surface before and after TTS nanofilm coating were examined by ellipsometry and contact angle goniometry, respectively. The same techniques were used to examine protein layer on nonmodified and TTS‐coated silicon surface. In addition, bright‐field optical microscopy and fluorescence spectrophotometry were used to provide visual, qualitative description of adsorbed proteins and the specific signal of fluorescence‐labeled bovine serum albumin (BSA), respectively, on bare and TTS‐coated silicon surface. Single‐component protein solution of four model proteins, namely BSA, human fibrinogen, bovine serum immunoglobulin G, and fibronectin, was prepared, and the adsorption responses of these four proteins on TTS nanofilm were examined, using nonmodified silicon surface as comparison. TTS substantially reduces the adsorption of all four proteins tested. Our results indicate that fluorocarbon‐containing TTS, once coated on surfaces, is an effective molecule for resisting protein adsorption. This will open up potential applications, particularly for silicon‐containing implant devices such as glass.